Obowiązek wniesienia wkładu w spółkach osobowych. Uwagi krytyczne - Jarosz, Iwo (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
An important feature of the regulation of partnerships in Polish law is that contributions are shaped as mandatory elements. Contributions need to be determined by the partners in the partnership agreement and made, i.e. transferred to the partnership’s assets. The peculiar aspect of partnerships which is their normative model providing for their lack of legal capacity prior to registration impedes obedience to this requirement in the case of certain contributions, such as real property, compelling the lawyers to construct elaborate theoretical mechanisms aiming to allow the making of such contributions. Parallel to the inadmissibility of contribution-less partnerships is the requirement that all partners make contributions. This text aims to examine and verify whether such shape of the partnerships’ model in Polish law, placing on each and every partner a requirement to determine in the partnership agreement and make contributions, is practically beneficial, given the aims it is deemed to pursue as well as the values it is supposed to protect. The author argues that the protection of creditors does not constitute proper justification for the contemporary regulation, as in the case of partnerships such protection is effected, above all, through the partners’ personal liability. The text shall also show that, given the lack of any threshold regulating the minimal contribution, the issues of protecting the legal relations from the establishment of entities failing to pass the so-called gravity test. The author will examine the provisions of Polish law — namely, the Code of Commercial Companies — employing the formal-dogmatic method. Comparative methods will also be utilized, allowing to construe further arguments based on the development of the European law and the laws of certain member states, showing the advisability and rationality of accepting the contributions-less model with respect to partnerships. Therefore, there exist convincing reasons to allow the establishment of contribution-less partnerships.
Keywords: partnerships; contributions; obligations; capital